2003
DOI: 10.1249/01.mss.0000058359.87713.99
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Cardiovascular Response to Shallow Water Exercise in Young and Older Women

Abstract: SWE elicited metabolic and cardiovascular responses that met ACSM's guidelines for establishing health benefits. Furthermore, older females may self-select a greater relative exercise intensity during SWE compared with younger counterparts when provided with the same verbal instructions and encouragement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 11 publications
0
42
2
2
Order By: Relevance
“…The participants, therefore, had a given sense of independence in establishing the intensity within the context and exertional boundaries of the Borg 6-20 RPE scale. This approach of self-regulating exercise intensity over a wide range of exertions during SWE is noteworthy given that most studies examining physiological responses during head out water immersion exercise have used cadence strategies, underwater treadmill, and on occasion instructional cues to regulate exertion (Barbosa et al, 2007, Benelli et al, 2004Campbell et al, 2003;D'Acquisto et al, 2001;Fujishima & Shimizu, 2003;Hoeger et al, 1995;Nagel et al, 2013;Pohl & McNaughton, 2003). Thus, this research provides valuable insight into absolute and relative cardiorespiratory responses for a broad continuum of participant controlled, perceptually regulated SWE efforts and on the usefulness of RPE for the regulation of SWE intensity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The participants, therefore, had a given sense of independence in establishing the intensity within the context and exertional boundaries of the Borg 6-20 RPE scale. This approach of self-regulating exercise intensity over a wide range of exertions during SWE is noteworthy given that most studies examining physiological responses during head out water immersion exercise have used cadence strategies, underwater treadmill, and on occasion instructional cues to regulate exertion (Barbosa et al, 2007, Benelli et al, 2004Campbell et al, 2003;D'Acquisto et al, 2001;Fujishima & Shimizu, 2003;Hoeger et al, 1995;Nagel et al, 2013;Pohl & McNaughton, 2003). Thus, this research provides valuable insight into absolute and relative cardiorespiratory responses for a broad continuum of participant controlled, perceptually regulated SWE efforts and on the usefulness of RPE for the regulation of SWE intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has yielded varying results regarding cardiorespiratory responses to maximal SWE (Campbell et al, 2003;Kruel et al, 2013;Silvers, Rutledge, & Dolny, 2007). For example, Kruel et al (2013) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, floating on water increases the elderly's ability to exercise (6). Floating on water, based on the principle of not tolerating body weight, can be used as an alternative to exercise on the ground (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Many water-based exercise studies have demonstrated improvements between programs of similar intensities in cardiovascular fitness, body composition, muscle strength, and flexibility (Campbell, D'Acquisto, D'Acquisto, & Cline, 2003;Gappmaier, Lake, Nelson, & Fisher, 2006;Ruoti, Troup, & Berger, 1994;Sato, Kaneda, Wakabayashi, & Nomura, 2007;Shono, Fujishima, Hotta, Ogaki, & Ueda, 2001;Takeshima et al, 2002;Tsourlou, Benik, Dipla, Zafeiridis, & Kellis, 2006;Wang, Belza, Thompson, Whitney, & Bennett, 2007). And while some aquatic exercise studies have shown improvements in balance measures, including functional reach (Simmons & Hansen, 1996), postural sway (Lord, Mitchell, & Williams, 1993;Suomi & Koceja, 2000), and step test (Devereux, Robertson, & Briffa, 2005), these studies did not have the specific aim to overload or challenge the targeted balance systems (i.e., sensory, central integrative, and motor).…”
mentioning
confidence: 99%